Brand Image and Customer Acquisition Strategy: A Case Study of an Islamic Microfinance Institution in Indonesia - Amiruddin, Amiruddin; Mujibno, Mujibno (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
Baitul Maal wat Tamwil (BMT), as part of Islamic Microfinance Institutions (IMFIs), plays a crucial role in enhancing financial inclusion in areas not yet reached by formal banking systems. This study aims to analyze the strategies for brand image development and customer acquisition at BMT Nusantara Capem Prenduan. A qualitative approach was employed, utilizing in-depth interviews, observation, and documentation as data collection techniques. The data were analyzed through the processes of data reduction, presentation, and conclusion drawing. The findings reveal that the brand image of BMT is shaped by three main factors: the reputation of the parent pesantren institution, technological innovation through the Mobile UGT application, and a religious-humanist door-to-door service approach. Communication strategies are carried out directly by staff members through an active and consistent personal approach. Even during the institutional rebranding phase, customer trust and loyalty remained intact. These findings underscore the importance of a strong institutional image and well-directed communication strategies in enhancing the competitiveness and sustainability of IMFIs amid the dynamics of the digital economy.